Colours Preferences in Housing Furniture by Two Different Culture Groups - Aylin Aras (International Journal of Architectural Engineering Technology, 2017)
Housing is an indicator of cultural identity of societies. Due to the housing they live, dwellers consciously or unconsciously give specific messages about their personal characteristics apart from their socio-cultural group. Colour preference which arouses different perceptions in people is one of the important elements in space design and is known to reflect the culture of dweller. It is thought that colours preferred for furniture which is one of the most important building stones of space is a cultural symbol and cultural differences are influential in the colour preferences of the furniture. With this study, colours preferences of dwellers in different socio-cultural groups for furniture in their housing which is the most prominent space reflecting culture were determined. Within the scope of study, survey and on-site monitoring were done in two different socio-culture groups and colours chosen by socio-cultural groups in their housing furniture were analyzed. As a result of the study it was examined that dwellers in two different socio-cultural groups used different colours in their housing furniture and differences between are revealed them.